Functional heterogeneity within the rodent lateral orbitofrontal cortex dissociates outcome devaluation and reversal learning deficits - Panayi, Marios C; Killcross, Simon (eLife, 2018)
The orbitofrontal cortex (OFC) is critical for updating reward-directed behaviours flexibly when outcomes are devalued or when task contingencies are reversed. Failure to update behaviour in outcome devaluation and reversal learning procedures are considered canonical deficits following OFC lesions in non-human primates and rodents. We examined the generality of these findings in rodents using lesions of the rodent lateral OFC (LO) in instrumental action-outcome and Pavlovian cue-outcome devaluation procedures. LO lesions disrupted outcome devaluation in Pavlovian but not instrumental procedures. Furthermore, although both anterior and posterior LO lesions disrupted Pavlovian outcome devaluation, only posterior LO lesions were found to disrupt reversal learning. Posterior but not anterior LO lesions were also found to disrupt the attribution of motivational value to Pavlovian cues in sign-tracking. These novel dissociable task- and subregion-specific effects suggest a way to reconcile contradictory findings between rodent and non-human primate OFC research.
Keywords: orbitofrontal cortex; outcome devaluation; reversal learning; autoshaping; Pavlovian learning; outcome identity